Acupuntura e gravidez: medicina oriental como aliada no tratamento de dor lombar - Eveliny Silva Martins; Régia Christina Moura Barbosa Castro; Lígia Maria Alves Rocha; Ana Karina Bezerra Pinheiro (Universidade Federal do Ceará, 2017)
Objective: to identify scientific evidence in the literature on the effect of acupuncture for the relief of low back pain during pregnancy. Methods: this is an integrative literature review. The bibliographic survey included articles indexed in the portal of six databases, using controlled keywords. Results: seven articles published in English were included. The studies using acupuncture for low back pain have been successful in reducing pain, as well as increased mobility, improved sleep, a sense of well-being, increased capacity for some physical activities and improved emotional reactions of pregnant women. Conclusion: acupuncture contributed to the reduction of low back pain in the pregnant women, among other benefits, contributing to the promotion of health in a pleasurable, simple, practical, risk-free, cheap and cost-effective way.